Improvement in Mung Bean Peptide on High-Fat Diet-Induced Insulin Resistance Mice Using Untargeted Serum Metabolomics - Li, Lina; Tian, Yu; Feng, Yuchao; Zhang, Shu; Jiang, Yingjun; Zhang, Yiwei; Zhan, Yuanyuan; Wang, Changyuan (Frontiers in Nutrition, 2022)
This study aimed to elucidate the potential regulatory mechanism of mung bean peptides (MBPs) on glucolipid metabolism in insulin-resistant mice induced by high-fat diet (HFD) using untargeted serum metabolomics, enzyme linked immunosorbent assay (ELISA), intraperitoneal injection glucose tolerance test (IPGTT), insulin tolerance test (IPITT), and  hematoxylin-eosin staining (H&E). The regulatory effect of MBPs for alleviating insulin resistance was studied by measuring body weight, fasting blood glucose (PBG) and serum insulin levels, C-peptide levels, inflammatory and antioxidant factors, and histopathological observation of C57BL/6 mice. The experimental results showed that dietary intervention with MBPs (245 mg/kg/d) for five weeks significantly relieved insulin resistance in HFD mice. The body weight, insulin resistance index, and the levels of FBG, C-peptide, IL-6, TNF-α, and MDA in the serum of HFD mice significantly decreased (P <0.05). Conversely, SOD content and pancreatic β cell function index significantly increased (P <0.05), and the damaged pancreatic tissue was repaired. One biomarker associated with insulin resistance was glycine. In addition, there were four important differential metabolites: pyroglutamate, D-glutamine, aminoadipic acid, and nicotinamide, involved in 12 metabolic pathway changes.It was found that MBPs may regulate amino acid, glycerol phospholipid, fatty acid, alkaloid, and nicotinamide metabolism to regulate the metabolic profile of HFD mice in a beneficial direction.